Peranan PBM PT Wahana Intradermaga Niaga pada Proses Bongkar Curah Kering di Pelabuhan Belawan - Supriyadi Supriyadi; Yursal Yursal; Meriah Kita Deliani (PPIMAN Pusat Publikasi Ilmu Manajemen, 2025)
This paper is to determine the Role of PBM Wahana Intradermaga Niaga in the Dry Bulk Unloading Process at PT. Pelabuhan Belawan. Unloading activities are activities to unload goods from the ship's hold to the dock in the ship's hull or vice versa (stevedoring), activities to move goods from the dock using a conveyor to the warehouse/stacking yard or vice versa (cargodoring) and activities to pick up goods from the warehouse/yard carried onto a truck or vice versa (receiving/delivery). A dry bulk carrier is a ship specifically designed to be able to transport various dry bulk loads. In the distribution of dry bulk cargo there is an unloading process. Unloading aims to lower and raise goods from the ship to the port or vice versa. And in supporting this goal requires unloading equipment. The unloading equipment in question comes from the port. In carrying out the unloading process, MV. S Grace has obstacles in carrying out unloading. So that the purpose of unloading is not achieved optimally. Therefore, an analysis is needed to determine the factors that inhibit the productivity of dry bulk unloading so that unloading activities can run optimally. From the results of reading and observing this paper, the author states that the implementation of unloading has inhibiting factors, namely external factors. Crane breakdown and bad weather are inhibiting factors in the dry bulk unloading process. Based on these factors, it has an impact on unloading delays that are not according to schedule and increase ship queues. Therefore, the author suggests that port operators or ship crews carry out routine maintenance on the equipment used for loading and unloading so that dry bulk loading and unloading can run optimally. This paper uses the field research method and the library research method (data collection from the library).